A Microcalorimetric Method for Studying the Biological Effects of Mg2+ Ion on Recombinant Escherichia coli - Fan, D.-D (Array, 2008)
Summary: Power-time curves of growing recombinant Escherichia coli B1 cell suspensions, treated with different concentrations of Mg2+, were recorded by microcalorimeter. The extent of the stimulatory effect of Mg2+ on the growth of recombinant E. coli B1 was compared by reference to the changes in the values of the growth rate coefficient of bacteria (k), the time of reaching the maximum effect in the log phase (tD), the time of maintaining the maximum effect in the stationary period (tS), and the maximum thermal power during the entire bacterial growth (Pm) at different Mg2+ doses and the optimal Mg2+ dose was calculated. The experimental results revealed that when Mg2+ mass concentration reached γ = 2.2 mg mL-1, the stimulatory effect is the greatest. With more Mg2+ (γ > 2.2 mg mL-1) added, the promotive effect would decrease drastically